KEBAYA SEBAGAI MEDIA PRESENTASI DIRI PEREMPUAN BALI DI KELURAHAN UBUD, GIANYAR - Aprillia Dewi, Putu Setia; Kebayantini, Ni Luh Nyoman; Ranteallo, Ikma Citra (JURNAL ILMIAH SOSIOLOGI (SOROT), 2015)
ABSTRACT Cultural and religious ceremonies are an inseperable part of the life of Balinese people. Numerous ceremonies that need to be done by Balinese people indirectly makes kebaya an important clothing. This research describes different ways that are done by Balinese women in Ubud Village to create ideal impressions through their kebaya. The concept of dramaturgy by Erving Goffman and qualitative methods are used to portray this phenomenon. In ceremonies that bring happiness Balinese women usually use kebaya in bright colors. However, in ceremonies that cause sadness, they prefer to use kebaya in darker colors. White or yellow kebaya are usually used for religious ceremonies. Thus, Balinese people in Ubud use different kinds of kebaya for different ceremonies. As the front stage, Balinese women will wear new kebaya with high heels, makeup and hairdo to represent their concept of a beautiful and ideal appearance. On the other hand, back stage is various activities to prepare for their appearance in the front stage. This activity includes buying kebaya, going to the salon, and exercising. These activities are done to prepared beautiful and ideal appearance when they interact with others, because essentially every human being wants to represent themselves to others. Key words: Balinese women, kebaya, cultural and religious ceremonies, ideal impression